Peningkatan Keterampilan Membaca Pemahaman melalui Metode Pembelajaran SQ3R bagi Siswa Kelas IV SD GMIM 12 Manado - Sobon, Kosmas; Oktafiani Sigarlaki; Patrisia Hana Supit (Pengembangan Pendidikan dan Pembelajaran Sekolah Dasar, 2023)
The purpose of this study was to improve elementary school students' reading comprehension skills through the application of the SQ3R learning method. This research uses classroom action research (CAR). The research location is SD GMIM 12 Manado. The application of the SQ3R learning method according to the results of the research analysis showed that the reading comprehension skills of fourth grade students at SD GMIM 12 Manado experienced a significant increase. These results are based on an analysis review starting from the pre-cycle with a completeness of 12.5%. Although the percentage of cycle I achievement at meeting 1 was the same as pre-cycle achievement (12.5%), at meeting 2 it experienced an increase (37.5%) but the increase was not yet significant in achieving the minimum completeness requirements. However, different results for cycle II meeting 1 actually showed 75% completeness with an average score of 76.5 and increased after meeting 2 with an average score of 84.8 or 100% of students who achieved the minimum requirements for learning success required.